TRANSFORMING FINANCIAL INSTITUTIONS THROUGH DATA-DRIVEN DECISION-MAKING: A CASE OF VIDARBHA REGION - Tanguturi, Raja Naga Vardhan; Muley, Anand A (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Given the constant change in the financial industry environment, the use of DDDM as a key way of increasing productivity, managing risks, and improving customers’ satisfaction has been adopted. This paper focuses on how DDDM is influencing financial institutions for the Vidarbha region of Maharashtra to adopt the analytical tools like data analytics, artificial intelligence and machine learning for improving the financial decision making. The study therefore develops a blend of quantitative and qualitative data in ascertaining the level of DDDM implementation and outcomes on financial performance. The important areas of the submission of big data are risk management, lending, credit risk, fraudulent behavior detection, and customer relationship management. The research also discusses antioxidants like data security, constraint infrastructures, and scope confinements on financial organizations that may slow the adoption of data analytics. This paper presents how DDDM supports innovation, maps a better understanding of financial decisions, and increases customer-centric services. Various suggestion and recommendation has been made at the end of study for how the financial institutions can effectively adopting data driven technologies for the sustainable growth and competitive advantage in the Vidarbha region.